Does 'When' really feel more certain than 'If'? Two failures to replicate Ballard and Lewandowsky (2015). Issue 7 (10th July 2019) - Sleeth-Keppler, David; Lewandowsky, Stephan; Ballard, Timothy; Myers, Teresa A.; Roser-Renouf, Connie; Maibach, Edward
Abstract : We report on two independent failures to conceptually replicate findings by Ballard & Lewandowsky (Ballard and Lewandowsky 2015 Phil. Trans. R. Soc. A 373, 20140464 (doi:10.1098/rsta.2014.0464)), who showed that certainty in, and concern about, projected public health issues (e.g. impacts of climate change) depend on how uncertain information is presented. Specifically, compared to a projected range of outcomes (e.g. a global rise in temperature between 1.6°C and 2.4°C) by a certain point in time (the year 2065), Ballard & Lewandowsky (Ballard and Lewandowsky 2015 Phil. Trans. R. Soc. A 373, 20140464 (doi:10.1098/rsta.2014.0464)) showed that focusing people on a certain outcome (a global rise in temperature of at least 2°C) by an uncertain time-frame (the years 2054–2083) increases certainty in the outcome, and concern about its implications. Based on two new studies that showed a null effect between the two presentation formats, however, we recommend treating the projection statements featured in these studies as equivalent, and we encourage investigators to find alternative ways to improve on existing formats to communicate uncertain information about future events.